PENGGUNAAN MEDIA BAHAN ALAM UNTUK MENINGKATKAN KREATIVITAS ANAK - Fauziah, Nadia (JIV-Jurnal Ilmiah Visi, 2013)
The purpose of this research is to improve the creativity of children aged 5-6 years through natural materials in PAUD Bestari, Gunungsindur, Bogor. The research conducted in November 2012 applied action research approach two cycles. Each cycle consists of planning, acting, observing and reflecting. The research subject were eleven kindergarten children having creativity problems. The final result of the overall data analysis indicates the hypothesis is accepted meaning that using natural materials can improve the creativity of children aged 5-6 years old.